A training support system for table tennis service using Kinect - Tamaki, S.; Nakamura, J.; Saito, H. (International Journal of Table Tennis Sciences, 2013)
In this paper, a system which provides data about table tennis service is proposed. The system reconstructs 3D trajectory of a ball and obtains the features of the service. In addition, the system provides the video in which player served without any operations. The system is comprised of a Microsoft Kinect and an ordinary PC. Experimental results show that the system can provide videos and following kinds of information: bouncing position, velocity and maximum height of a service.